Statistics in regulatory science - Chow, Shein-Chung, 1955- (Boca Raton : CRC Press, 2018)
"The proposed book will focus on practical issues in pharmaceutical/clinical research and development from both regulatory and scientific perspectives. The book will outline and clarify those issues that have been commonly misused in the subject area of regulatory science"--
Totality-of-the-evidence -- Hypotheses testing versus confidence interval -- Endpoint selection -- Non-inferiority margin -- Missing data -- Multiplicity -- Sample size -- Reproducible research -- Extrapolation -- Consistency evaluation -- Drug products with multiple components -- Adaptive trial design -- Selection criteria in adaptive dose finding -- Generic drugs and biosimilars -- Precision and personalized medicine -- Big data analytics -- Rare disease drug development.
OCLC-licensed vendor bibliographic record.
Keywords: Drugs -- Testing; Clinical trials -- Statistical methods; Pharmacy -- Research; Research -- Statistical methods; MATHEMATICS / Probability & Statistics / General; MEDICAL / Pharmacology; REFERENCE / General